Tanshinone IIA Protects Against Cerebral Ischemia Reperfusion Injury by Regulating Microglial Activation and Polarization via NF-κB Pathway - Song, Zhibing; Feng, Jingjing; Zhang, Qian; Deng, Shanshan; Yu, Dahai; Zhang, Yuefan; Li, Tiejun (Frontiers in Pharmacology, 2021)
Tanshinone IIA, a fat-soluble diterpenoid isolated from Salvia miltiorrhiza Bunge, has been shown to attenuate the cerebral ischemic injury. The aim of this study was to examine the effects on neuroprotection and microglia activation of tanshinone IIA. Male Sprague-Dawley (SD) rats were subjected to middle cerebral artery occlusion (MCAO). We found that tanshinone IIA significantly reduced infarction volume, alleviated neuronal injuries, reduced the release of TNF-α, IL-1β, and IL-6, increased SOD activity, and decrease the content of MDA in MCAO rats. Hematoxylin and eosin (H&E) staining, Nissl staining, TUNEL staining and immunofluorescence staining showed that tanshinone IIA improved the distribution and morphology of neurons in brain tissues and reduced apoptosis. In addition, Co-immunofluorescence staining of rat brain tissues and the mRNA expression levels of CD11b, CD32, iNOS, and Arg-1, CD206, IL-10 in BV2 cells indicated that tanshinone IIA can downregulate M1 microglia and upregulate M2 microglia in MCAO rats. Further, BV2 microglial cells were subjected to oxygen-glucose deprivation (OGD), the protein expression levels were detected by western blot. Tanshinone IIA inhibited the expression levels of NF-κB signaling pathway related proteins. Taken together, this study suggested that tanshinone IIA modulated microglial M1/M2 polarization via the NF-κB signaling pathway to confer anti-neuroinflammatory effects.